2006
DOI: 10.1128/iai.00991-06
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of Helicobacter pylori NapA in Inducing and Combating Oxidative Stress

Abstract: Neutrophil-activating protein (NapA) has been well documented to play roles in human neutrophil recruitment and in stimulating host cell production of reactive oxygen intermediates (ROI). A separate role for NapA in combating oxidative stress within H. pylori was implied by studies of various H. pylori mutant strains. Here, physiological analysis of a napA strain was the approach used to assess the iron-sequestering and stress resistance roles of NapA, its role in preventing oxidative DNA damage, and its impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 52 publications
5
92
3
Order By: Relevance
“…Deficiency of a range of antioxidant enzymes, including Hp-SOD, KatA, Hp-Tpx, and AhpC, results in a compensatory increase in NapA production (76), suggesting that it may function as a secondary antioxidant that becomes important when other defenses are overwhelmed. This is supported by the fact that NapA mutant strains of H. pylori are able to colonize mice normally (99), indicating that the enzyme is not required for survival and that some functional redundancy may be present. Although the precise mechanism of its antioxidant activity is unknown, it is possible that the iron-sequestering properties of NapA may help prevent secondary ROS formation from superoxide (99).…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Deficiency of a range of antioxidant enzymes, including Hp-SOD, KatA, Hp-Tpx, and AhpC, results in a compensatory increase in NapA production (76), suggesting that it may function as a secondary antioxidant that becomes important when other defenses are overwhelmed. This is supported by the fact that NapA mutant strains of H. pylori are able to colonize mice normally (99), indicating that the enzyme is not required for survival and that some functional redundancy may be present. Although the precise mechanism of its antioxidant activity is unknown, it is possible that the iron-sequestering properties of NapA may help prevent secondary ROS formation from superoxide (99).…”
supporting
confidence: 50%
“…This is supported by the fact that NapA mutant strains of H. pylori are able to colonize mice normally (99), indicating that the enzyme is not required for survival and that some functional redundancy may be present. Although the precise mechanism of its antioxidant activity is unknown, it is possible that the iron-sequestering properties of NapA may help prevent secondary ROS formation from superoxide (99). When ironloaded, NapA can also bind to DNA with great affinity and, therefore, may play a role in protecting DNA from oxidative damage.…”
supporting
confidence: 50%
“…ROS production is significantly decreased in gastric mucosa of patients with H pylori successfully eradicated [33] . It has also been shown that HP-NAP can be involved in extravasation of leukocytes, and ROS can play a role in the carcinogenic process in gastric mucosa during chronic H pylori infection [34,35] , indicating that HP-NAP may be a risk factor for H pylori-associated gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In Helicobacter pylori NapA plays a dual role in pathogenesis: in colonization and in protection against oxidative damage (Wang et al, 2006). As a protein that binds iron, it may thus serve as a primitive siderophore for mycoplasmas, although in previous work, napA was not transcriptionally responsive to changes in iron concentration in M. hyopneumoniae (Madsen et al, 2006b) as has been shown in other bacterial pathogens (Mey et al, 2005).…”
Section: Resultsmentioning
confidence: 66%